The challenge of recruiting diverse populations into health research: an embedded social science perspective. Issue 3 (3rd July 2022) - Outram, Simon M.; Ackerman, Sara L.; Norstad, Matthew; Koenig, Barbara
Abstract : Addressing health disparities has become a central remit for conducting health research. In the following paper, we explore the conceptual and methodological challenges posed by the call to recruit medically underserved populations. This exploration of challenges is undertaken from the perspective of social science researchers embedded in a large clinical genomics research study. We suggest that these challenges are found in respect to the development of recruiting strategies, analysis of the data in respect to understanding and interpreting the experiences of being medically underserved, and in comparing the experiences of being medically underserved compared to not being underserved. By way of conclusion, it is argued that there is an important role for social scientists with large health research studies which, if achieved successfully, can benefit study teams and society as a whole.